PELAKSANAAN DESENTRALISASI ASIMETRIS DALAM TATA KELOLA PEMERINTAHAN DAERAH DI ERA DEMOKRASI - Andhika Yudha Pratama (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: after the fallen of Soeharto centralistic government, there’s revolution wave in Indonesia.Changing in government system was one of cange wanted by people. Centralistic immedietly replacedwith Decentralistic.This decentralistic system later creates new variant : asymetrical decentralization.Asymemetrical decentralization are given to special province in order to create publicwelfare and maintain the unity of NKRI. This paper hopes to give alternative view of asymetricaldecentralization in Indonesia.Keywords : asymetrical decentralization, democratic government system